A utilização de tecnologias educacionais e experimentos na formação continuada de professores que trabalham com o ensino das ciências da natureza e matemática no ensino médio em Alta Floresta - MT - Santos, Simone José Aparecida da Silva (2016)
Through this work, was sought to investigate the conception that teachers have regarding the use of educational technologies and experiments in teaching and learning process of physical concepts. The research subjects were teachers who work the disciplines of physics and mathematics in state schools that receive high school students in the municipality of Alta Floresta - MT. During was observed the contributions and challenges of continued education of these professionals regarding the use of educational software and experiments in their teaching practices. Formations done at CEFAPRO were also reported, among them the use of the software GeoGebra. Through them Geogebra was explored as a resource for the study of the geometry and the study of quadratic functions. As a product of this master, it was designed and developed a proposal for continuing education, which addressed the experimentation in building concepts in the field of natural sciences and Mathematics and the need to work in a meaningful and contextualized way. At the development was sought to promote use of interdisciplinary experiments, focusing on Geometrical optics and use of the optical microscope.